Pembimbingan Mahasiswa Peserta Kegiatan Pengenalan Lapangan Persekolahan (PLP) Di SDN Kalangan Kapanewon Kasihan Kabupaten Bantul - Rochaendi, Endi; Ariyani, Yusinta Dwi; Sari, Indah Perdana; Kholik, Nur (Bangun Desa: Jurnal Pengabdian Masyarakat, 2023)
To form prospective teachers who have the competence to understand students, manage the learning process, master scientific material in the field of education and the learning process and have the attitude and character of the teacher, the PGSD Study Program at Alma Ata University carries out schooling field introduction activities in elementary schools. Introduction to the School Field is an activity in the process of observation/observation and apprenticeship to learn and understand the implementation of the learning process in the classroom and other educational management, including practicing it in teaching and learning activities with students. One of the target objects of the school field introduction activity was carried out at the Kalangan Elementary School, Kasihan District, Bantul Regency. For the successful implementation of field introduction to schooling, mentoring activities are needed, carried out by field supervisors with multiple roles as facilitators, educators, mediators, and advocators. In their daily practice, the field supervisors have successfully formed and increased students' capacity to act and behave as curricular operations, intersection roles, assist, and internship roles in educational units with mentoring through consulting, assistance, and facilitation activities. In this connection, schooling field introduction activities have been maximally realized by established norms, standards, procedures, and criteria. Keywords: mentoring, introduction to the school field, the role of the supervising lecturer